Case Report: Anatomic Pathology of Bali Cattle Liver Infested with Fasciola gigantica - Sewoyo, Palagan Senopati; Purwanti, Ni Luh Lasmi; Evan, Samuel (Universitas Airlangga, 2024)
Infectious diseases pose a significant threat to livestock health and productivity, particularly in developing countries. Fasciolosis, caused by infestation of Fasciola sp., is one such disease of concern. This case report focuses on the anatomic pathologic changes observed in the liver of Bali cattle infested with Fasciola gigantica. The cattle involved in this study were Bali cattle slaughtered at the Mambal Slaughterhouse in Badung, Bali, Indonesia between December 2021. During the specified period, 2 out of the 16 slaughtered cattles tested positive for Fasciola gigantica, representing an infection rate of 12.5%. The primary objective of composing this article is to disseminate information pertaining to the anatomical and pathological alterations observed in Bali cattle as a consequence of fasciolosis. Regarding the observation, the liver exhibited hepatomegaly, characterized by enlarged size and blunt edges, and adult flukes were found in the bile ducts. The surface of the liver parenchyma displayed proliferation of connective tissue, and there was evidence of enlarged portal lymph nodes. Based on these findings, it can be concluded that the Bali cattle in this case report were afflicted with fasciolosis.